Investigation on creep behavior of welded joint of advanced 9%Cr steels. Issue 2 (12th December 2014) - Meng, Donghai; Lu, Fenggui; Cui, Haichao; Ding, Yuming; Tang, Xinhua; Huo, Xin
Abstract: Abstract : The creep behavior of advanced 9%Cr-1 (BM1) and advanced 9%Cr-2 (BM2) dissimilar welded joints was investigated in this paper, and also the microstructures were elaborately characterized. Based on the fitting with MATLAB, a 3-D curved surface describing the primary and steady-state creep stage was achieved. The comparison of the microstructures of the precreep and aftercreep welded joints shows that δ-ferrite distribution in the heat affected zone (HAZ) of BM2 side plays an important role in determining creep rupture strength. Fracture occurred at the overtempered heat affected zone (OT-HAZ) adjacent to BM2 after creep tests at 538 °C under different stress loads. Microhardness tests revealed that the OT-HAZ adjacent to BM2 has the lowest hardness value compared with the whole welded joint. Numerous creep voids occurring around δ-ferrite, carbides, and grain boundaries were observed on the specimen after creep test. They concentrated and grew up to microcracks, and then induced the fracture at OT-HAZ. Many second phases were also observed in the grain boundary after creep, and the tempered martensite boundaries in the HAZ gradually become obscure as the creep time increases.